2013
DOI: 10.13080/z-a.2013.100.021
|View full text |Cite
|
Sign up to set email alerts
|

Genotype and microclimate conditions influence ripening pattern and quality of blackcurrant (Ribes nigrum L.) fruit

Abstract: Blackcurrant (Ribes nigrum L.) fruit is valued for its content of nutritional compounds essential for human health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
17
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 24 publications
5
17
2
Order By: Relevance
“…Similarly to our findings, a low fruit weight of the cultivar 'Ben Alder' has been observed in trials executed in Poland (Pluta et al, 2005;Ochmian et al, 2014). In earlier longterm studies, the genotype 'Asker' has shown low yearly variation in fruit weight (Kaldmäe et al, 2013), but in the present experiment the differences between years are more notable, although having no effect on the fruit weight of cultivars 'Ben Alder' and 'Pamyati Vavilova'. The genotypes with large berries, such as 'Intercontinental', 'Karri' and 'Mairi' had a significantly lower fruit weight in the organic cultivation method as compared to the conventional, and in previous studies 'Intercontinental' has shown high yearly differences as well (Kaldmäe et al, 2013).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Similarly to our findings, a low fruit weight of the cultivar 'Ben Alder' has been observed in trials executed in Poland (Pluta et al, 2005;Ochmian et al, 2014). In earlier longterm studies, the genotype 'Asker' has shown low yearly variation in fruit weight (Kaldmäe et al, 2013), but in the present experiment the differences between years are more notable, although having no effect on the fruit weight of cultivars 'Ben Alder' and 'Pamyati Vavilova'. The genotypes with large berries, such as 'Intercontinental', 'Karri' and 'Mairi' had a significantly lower fruit weight in the organic cultivation method as compared to the conventional, and in previous studies 'Intercontinental' has shown high yearly differences as well (Kaldmäe et al, 2013).…”
Section: Discussionsupporting
confidence: 89%
“…In earlier longterm studies, the genotype 'Asker' has shown low yearly variation in fruit weight (Kaldmäe et al, 2013), but in the present experiment the differences between years are more notable, although having no effect on the fruit weight of cultivars 'Ben Alder' and 'Pamyati Vavilova'. The genotypes with large berries, such as 'Intercontinental', 'Karri' and 'Mairi' had a significantly lower fruit weight in the organic cultivation method as compared to the conventional, and in previous studies 'Intercontinental' has shown high yearly differences as well (Kaldmäe et al, 2013). Trials in Norway have revealed the positive effect of precipitation and the negative impact of temperature on fruit weight (Woznicki et al, 2015a), which correspond to our results.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…Lister et al [2002] determined the dependence of vitamin C content in black currants on production site, with higher levels found in northern countries than in southern countries. Kaldmae et al [2013] observed that vitamin C content is negatively correlated with temperature, and positively with rainfall, while Walker et al [2010] found that black currants grown on south facing slopes that received more warmth and solar radiation contained up to 20% more vitamin C than those grown on north facing slopes. Vagiri et al [2013] reported higher levels of vitamin C in currants grown in the south of Sweden compared to currants grown in the north of Sweden.…”
Section: Resultsmentioning
confidence: 99%
“…The level of anthocyanin compounds in blackcurrant fruit largely depends on the genotype, but can be modified under different climatic and environmental conditions (Hancock et al 2007). In addition to the bioactive compounds, the high quality of the fruit is determined by the soluble solids content, and the ratio between the amount of sugars and acids (Kaldmäe et al 2013). These compounds determine the quality and taste of blackcurrant berries (Bordonaba and Terry 2008), and are of particular importance in their production for the fresh fruit market.…”
Section: Introductionmentioning
confidence: 99%